Model Pengembangan Pelaksanaan Uji Kompetensi Berbasis Digital dalam Peningkatan Kualitas LSP di Perguruan Tinggi - Prastyana, Brahmana Rangga; Prasetyo, Aji; Putra, Very Ferdiansyah Eka (Southeast Asian Journal of Islamic Education Management, 2024)
The improvement of student competency in the Higher Education environment is carried out by the Professional Certification Institute (LSP), namely through competency test activities in the competency certification scheme it has. As a form of improving the quality of LSP, the development of digital-based competencies needs to be carried out so that it can be an alternative in implementing competency tests that are still guided by applicable regulations, upholding the principles of competency testing and are more effective and efficient. The purpose of this study is to develop a model for implementing competency test activities for all certification schemes in LSP, starting from registration to the pre-assessment stage. This research is a type of development research with a research and development (R and D) model. The procedure in development research uses steps including the stages of analysis, design, development, implementation, and evaluation. The subjects in this study were LSP implementers in Higher Education, in this case LSP P1 Universitas PGRI Adi Buana Surabaya. This study uses expert validation tests related to the content and products of the development. The results of a series of research activities based on trial evaluations are known to obtain an average score of eligibility of 3.81 with a maximum scale of 4 in the very good category. From the evaluation results, improvements are needed in the design aspects, namely the type of writing, the appearance of the background and the addition of videos as a guide for prospective assessors in this case students of Universitas PGRI Adi Buana Surabaya.